ROUTINE NASAL PACKING FOLLOWING SEPTOPLASTY IS IT NECESSARY - Naeem Akhtar (Journal of University Medical & Dental College, 2015)
ABSTRACT: OBJECTIVE: To evaluate and assess the need of routine anterior nasal packing after septoplasty. INTRODUCTION: Septoplasty for the symptomatic deflected nasal septum (DNS) is the commonest nasal operation performed all over the world. The most disliked part of the whole procedure on the part of the patient is post operative removal of nasal packing which is usually done after 24 – 48 hours. Some of the patients having symptomatic deflected nasal septum do not get operated or they delay their operation just because of fear of nasal packing removal. Many a times there is no bleeding at all at the end of operation but we still perform nasal packing because of danger of reactionary or primary bleeding. A variety of materials are being used for nasal packing, most of which are not evidence based. STUDY DESIGN: Descriptive non-interventional study. PLACE AND DURATION OF STUDY: This study was conducted in the department of ENT and Head & Neck Surgery at Allied Hospital Faisalabad over a period of 03 years from December 2010 to November 2013. PATIENTS AND METHODS: A total of 100 patients having symptomatic deflected nasal septum were included in this study. All patients underwent septoplasty with quilting sutures taken on the septum under local anesthesia. All data was analysed and computed by SPSS software, version 10. Chi square test was used to analyse the data. P values < 0.05 were considered statistically significant. RESULTS: 83 patients (83%) had no problem and so nasal packing was not done in these patients. On the other hand 17 patients (17%) needed nasal packing. Anterior nasal packing was performed in 09 patients (09%) at the end of procedure because of heavy bleeding during operation. 06 patients (06%) reported back within 24 hours due to reactionary bleeding and another 02 patients (02%) presented with septal hematoma in which we had to perform anterior nasal packing after drainage. All patients were satisfied at the end of 03 months. CONCLUSION: Routine use of nasal packing after septoplasty is not justified. Symptomatic deflected nasal septum can be safely treated with septoplasty without anterior nasal packing and by taking quilting sutures on the septum.